“Trampantojo” forums for the numerous breaches carried out by Ryanair in international flights - Carrizo Aguado, David (CUADERNOS DE DERECHO TRANSNACIONAL, 2019)
From the perspective of the international civil process, there is no doubt that the basic interest of the parties is predictability. This translates into the need to know beforehand, if differences arise, before which jurisdiction it would be necessary to assert rights. The Regulation (EU) 1215/2012 starts from a structured organization of the international judicial competence, distinguishing between exclusive forums, tacit or express submission, the forum of the domicile of the defendant, the special fórums by reason of the matter and the forums of protection. This structure assumes a hierarchical allocation of international judicial competence between the different Member States. In this way, prima facie should know the courts that are assigned their competence with exclusive scope and outside these cases, the courts can come to know through agreements attributing jurisdiction, either tacit or express, or, failing that match , either with the place of domicile of the defendant, or with any of the special fórums for reason of the matter. The present study examines a specific list of forums of international judicial competence that derive from an online purchase contract for international air tickets with the Ryanair company as a result of the novel and, why not, unprecedented pronouncement by the Luxembourg Court of 11 April 2019, subject ZX.
Keywords: determination of competent jurisdictional body; unspoken extension of competence; branch operation; electronic consumer; compensation for air delay